Understanding of the Experimental Concept of Radiation Absorption of Radioactive Materials - Prayogi, Soni; Silviana, Fitria; Zainuddin, Zainuddin (Universitas Sebelas Maret, 2023)
In this article, we discuss the experimental absorption of radioactive light radiation on various materials using Geiger Muller. Under certain conditions, Geiger Muller can be used to determine the absorption coefficient of a material. The radioactive rays observed in this experiment are gamma rays. Gamma rays are radioactive rays that have no charge so they cannot be deflected by magnetic or electric fields and have the greatest penetrating power. We made several important results on experimental studies of the absorption of gamma radiation passing through matter. Our results relate to the trend of the unexpected, measured intensity of radiation versus the thickness of the absorber, which confuses students and cannot be explained by many laboratory assistants. Finally, we believe that a distribution function is an effective tool for examining the contribution of the build-up factor in the Geiger Muller calculation of the measured radiation intensity.